Phenome-wide association studies across large population cohorts support drug target validation - Dorothée Diogo (Nature Portfolio, 2018)
Testing the association between genetic variants and a range of phenotypes can assist drug development. Here, in a phenome-wide association study in up to 697,815 individuals, Diogo et al. identify genotype–phenotype associations predicting efficacy, alternative indications or adverse drug effects.